Animal models for studying epithelial barriers in neonatal necrotizing enterocolitis, inflammatory bowel disease and colorectal cancer. Issue 4 (2nd October 2017) - Xing, Tiaosi; Camacho Salazar, Rolando; Chen, Yan-Hua
ABSTRACT: The intestinal epithelial cells line the luminal surface of the entire gastrointestinal tract which is crucial for the absorption of nutrients and prevention of pathogens entering from the external environment. The epithelial barrier plays an important role in organ development, disease pathogenesis, and aging. The major component of an epithelial barrier is the single columnar epithelium and tight junctions. Tight junctions are located at the most apical region of the junctional complex and contain many integral membrane proteins, such as occludin, the claudin family, and junctional adhesion molecules (JAMs). The disruption of intestinal epithelial barriers may lead to several pathophysiological conditions causing malabsorption of nutrition and chronic inflammation. In this review, we provide an update on the alterations of epithelial barriers associated with gut diseases using experimental animal models; we appraise the role of tight junctions in neonatal necrotizing enterocolitis (NEC), inflammatory bowel disease (IBD), and colorectal cancer; we also compare some common features as well as differences and similarities in the pathophysiology of intestinal inflammation in neonatal (NEC) and adult (IBD) gut.